The Effect of Recruitment Process, Compensation, and Work Motivation on Employee Performance at Ilianur Women and Children Hospital, Serang, Banten - Kemas Riskia Ramadhan (Majapahit Journal of Islamic Finance and Management, 2026)
This study examines the effects of the recruitment process, compensation, and work motivation on employee performance at Ilanur Mother and Child Hospital (RSIA Ilanur), Serang, Banten. The research adopts a quantitative approach with a descriptive and correlational research design. The population consists of 77 hospital employees, from which a sample of 65 respondents was determined using the Slovin formula and selected through a non-probability sampling technique. Data were collected using structured questionnaires and analyzed using descriptive statistics and inferential statistical methods, including t-tests and F-tests. The results indicate that the recruitment process has a positive effect on employee performance, as evidenced by a t-value of 0.270 with a significance level below 0.05. Compensation also shows a positive effect on employee performance, with a t-value of 1.919 and a significance level below 0.05. Furthermore, work motivation demonstrates a strong positive effect on employee performance, reflected by a t-value of 7.443 and a significance value of 0.000. Simultaneously, the recruitment process, compensation, and work motivation significantly influence employee performance, as indicated by an F-value of 25.462, which exceeds the F-table value of 2.730, with a significance level of 0.001. These findings suggest that effective recruitment, fair compensation, and strong work motivation are critical factors in improving employee performance in healthcare organizations.